2022
DOI: 10.1111/ecc.13686
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and sexual well‐being in breast cancer survivors undergoing immediate breast reconstruction: The mediating role of breast satisfaction

Abstract: Objective: This study aimed to explore (1) the levels of quality of life (psychosocial, physical and sexual well-being) and breast satisfaction in breast cancer patients (BCP) after immediate reconstruction (IR), considering surgery reason and surgical technique, and (2) the explanatory and predictive capacity of psychosocial well-being on breast satisfaction, and of both on sexual well-being.Methods: This prospective study included 36 BCP who underwent IR between June 2006 and December 2014.Results: Highest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…34 Gil-Olarte et al also reported that positive body image after reconstruction produced a signi cant, favorable effect on psychological well-being. 35 The evidence form the current study suggests that reconstruction improves body image and promotes psychological well-being in patients with breast cancer.…”
Section: Spousal Support Levels In the Women Diagnosed As Breast Cancermentioning
confidence: 62%
“…34 Gil-Olarte et al also reported that positive body image after reconstruction produced a signi cant, favorable effect on psychological well-being. 35 The evidence form the current study suggests that reconstruction improves body image and promotes psychological well-being in patients with breast cancer.…”
Section: Spousal Support Levels In the Women Diagnosed As Breast Cancermentioning
confidence: 62%
“…Malu did her reconstruction immediately after the mastectomy and she is satisfied with the result. The reconstruction surgery can often give women back their self-esteem, the feeling of being complete again and their self-image, in addition to helping to overcome the consequences of the disease (Inocenti et al, 2016;Márquez, Gil-Olarte, Molinero, & Bozal, 2022). However, it is important to remember that the way a woman sees her body before and after the changes caused by cancer can influence the way she sees herself after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there are documented psychological benefits from IBR ( 73 76 ) and patients awake from anaesthesia with two breasts, albeit one being a facsimile of a breast (i.e a breast mound). By contrast, patients must endure being flat-chested on one or both sides for a period of time whilst awaiting DBR.…”
Section: Whole Breast Reconstructionmentioning
confidence: 99%
“…Breast reconstruction can be performed at the time of mastectomy (immediate breast reconstruction [IBR]) or at any time after mastectomy (delayed breast reconstruction [DBR]). In recent years, IBR has gained wider acceptance with improved cosmetic results and reassuring evidence that reconstruction does not mask detection of recurrent disease (68)(69)(70)(71)(72).…”
Section: Whole Breast Reconstructionmentioning
confidence: 99%